2009
DOI: 10.1097/bpo.0b013e3181901c3a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Severity of Pediatric Osteomyelitis Attributable to Methicillin-Resistant Versus Methicillin-Sensitive Staphylococcus aureus

Abstract: Our results support the hypothesis that MRSA produces more severe bone infection and is likely to require more aggressive surgical and medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 32 publications
(25 reference statements)
2
52
0
2
Order By: Relevance
“…These parameters were significantly different (p < 0.01) in MRSA group of acute haematogenous osteomyelitis comparing with MSSA, other culture positive cases and culture negative groups. 15 One of the reasons of not having significant difference among the most of the clinical and haematological parameters of MRSA and non MRSA bone and joint infections analysed in our study may be having 57% population of our study <1 year age out of which 78% were <1 month. These patients have immature immune system and thereby may have normal temperature, WBC and other inflammatory markers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These parameters were significantly different (p < 0.01) in MRSA group of acute haematogenous osteomyelitis comparing with MSSA, other culture positive cases and culture negative groups. 15 One of the reasons of not having significant difference among the most of the clinical and haematological parameters of MRSA and non MRSA bone and joint infections analysed in our study may be having 57% population of our study <1 year age out of which 78% were <1 month. These patients have immature immune system and thereby may have normal temperature, WBC and other inflammatory markers.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that patients with MRSA infection show significant increase in serum levels of inflammatory markers, grade of temperature and extent of osteoarticular involvement compared to patients with non MRSA infection. 9,15,16 Hawkshed et al performed a retrospective analysis of 71 cases of age four months to 19 years and found that in MRSA acute haematogenous osteomyelitis the median duration of elevated temperature was 3.06 days, the temperature was 102.03 F, WBC count was 13,740/mm 3 , ESR was 73.5 mm/h and CRP was 9.5 mg/L. These parameters were significantly different (p < 0.01) in MRSA group of acute haematogenous osteomyelitis comparing with MSSA, other culture positive cases and culture negative groups.…”
Section: Discussionmentioning
confidence: 99%
“…An attempt to validate this clinical prediction algorithm among 58 patients (MRSA, n ϭ 16; MSSA, n ϭ 42) in Phoenix, AZ, found the algorithm to have a poor predictive value (503). Without genotyping data, it seems likely that the study by Ju et al and previous studies that also compared cases of acute OM due to MRSA versus MSSA (498,502,504,505) found discriminators between USA300 and other S. aureus clones rather than between MRSA and MSSA per se.…”
Section: Osteoarticular Infections In Childrenmentioning
confidence: 93%
“…Furthermore, the prevalence of K kingae seems to vary geographically, perhaps accounting in part for our findings. 6,[30][31][32][33] Continued surveillance of the microbiology of AHO is needed to inform empirical therapy in the future.…”
Section: Figurementioning
confidence: 99%